THE EFFECT OF PARENTAL ATTENTION ON THE DEVELOPMENT OF CHILDREN’S EDUCATION AND MORALS IN TONTONAN HAMLET, TANETE VILLAGE - Mukhamad Akbar (IAI DDI Mangkoso, 2025)
Education is the process of developing one's knowledge or self-potential through existing levels of education, as well as through learning provided and even training. Education can be carried out by families, communities, and governments, both at school and outside of school. Meanwhile, morality is a teaching that contains the development of morals and human behavior and manners. This study aims to find out how parents affect the daily education and morals of children in Tanete Village Spectacle Hamlet, with the background that the people of Tanete Village Spectacle Hamlet are farmers who need every day spent in the garden to make money. Thus, early childhood becomes a victim of a lack of parental attention in daily life, so that no one controls their daily life and has an impact on early childhood morale. The conclusion of this study is that parents' attention to early childhood in Tontonan Hamlet, Tanete Village, is not what is prioritized by the residents there, but what is prioritized is the economic results and livelihood of the local community, so that early childhood only gets attention at school. There are not many parents who entrust their children to Islamic boarding schools with the aim of getting more attention there, where parents are more free to earn a living and carry out their habits in the hamlet of spectacle, Tanete village.